Neural mechanisms of reward-guided behavioural flexibility - Hall-McMaster, S (2020)
Pursuing goals requires us to be flexible. When engaged in goal-directed behaviour, such flexibility is guided by the prospect of reward. The first part of this thesis examines how reward prospect influences flexible updating of task rules, needed to switch between tasks. Chapter 2 investigates how sequential changes in reward prospect influence rule updating across three behavioural experiments. This chapter shows inconclusive evidence for the hypothesis that sequential increases in reward prospect promote flexible rule updating. Chapter 3 examines the neural representation of task rules using multivariate pattern analyses of electroencephalographic data. This shows that high reward prospect boosts the neural encoding of task rules on trials where rules must be flexibly updated but not on trials where rules are repeated. The second part of this thesis examines how reward prospect is used to guide decisions about when to switch from option to another. Chapter 4 examines the theoretical implications of using reward properties of specific alternatives to guide switch decisions. Simulations show that decisions to switch based on specific alternatives tend to produce earlier switch decisions and higher reward overall than switch decisions based on average reward rates. Chapter 5 uses multivariate pattern analyses of electroencephalographic data to investigate how people decide when to switch to a specific option, in the absence of direct sensory cues to indicate its changing value. This reveals preliminary evidence that people track the hidden reward prospect for switching and use this information to regulate switch behaviour. Chapter 6 discusses implications of these results and bridges across cognitive control and decision making studies.